Angiotensin converting enzyme inhibitors or angiotensin antagonists in diabetic nephropathy - Grabowski, Marcin; Filipiak, Krzysztof J.; Opolski, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2005)
Diabetic nephropathy occurs is the single leading cause of end-stage renal disease. Intensive diabetes management has been shown in large prospective randomized studies to delay the onset of microalbuminuria and the progression of micro- to macroalbuminuria. In the treatment of both micro- and macroalbuminuria, either angiotensin converting enzyme inhibitors or angiotensin II antagonist should be used except during pregnancy.